2018
DOI: 10.1302/2046-3758.72.bjr-2017-0082.r1
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of microRNA during fracture healing in diabetic rats

Abstract: ObjectivesDiabetes mellitus (DM) is known to impair fracture healing. Increasing evidence suggests that some microRNA (miRNA) is involved in the pathophysiology of diabetes and its complications. We hypothesized that the functions of miRNA and changes to their patterns of expression may be implicated in the pathogenesis of impaired fracture healing in DM.MethodsClosed transverse fractures were created in the femurs of 116 rats, with half assigned to the DM group and half assigned to the control group. Rats wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 34 publications
5
29
0
Order By: Relevance
“…mirnas have previously attracted attention as potential biomarkers of BN (36)(37)(38)(39), warranting the identification of deMs in Bn patient bone tissue samples. The present study revealed that mir-1225-5p is highly expressed in Bn tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…mirnas have previously attracted attention as potential biomarkers of BN (36)(37)(38)(39), warranting the identification of deMs in Bn patient bone tissue samples. The present study revealed that mir-1225-5p is highly expressed in Bn tissues.…”
Section: Discussionmentioning
confidence: 99%
“…elevated plasma mir-339-5p levels have previously been identified as a biomarker of lung adenocarcinoma (39) and linked to increased activation of the protein B-cell lymphoma 6 (41), whereas upregulation of the resulting protein suppresses PRCP expression (42,43). Consistent with these findings, the present study revealed that mir-339-5p was upregulated in Fc, fold-change; mirna, microrna.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, investigators designed a new scoring system to assess the miRNA contribution to impaired fracture healing, and 11 miRNAs were identified to impairing fracture healing in aged female mice [14] . The expression of five miRNAs (miR-140-3p, miR-140-5p, miR-181a-1-3p, miR-210-3p and miR-222-3p) is altered in diabetic mice with impaired fracture healing when compared to normal mice [15] . As SPC3649, the first miRNA-targeting drug for the treatment of hepatitis C virus infection, is being investigated in clinical trials [16] , we speculate that promoting or inhibiting miRNA function is a potential therapy for nonunion.…”
Section: Genetic Factorsmentioning
confidence: 99%
“…miR-148a and miR-21-5p target pivotal genes involved in bone development, modeling, and remodeling (e.g., wingless-type MMTV integration site family, member 1 (WNT1), and transforming growth factor-β 2 (TGF-β2)), thus suggesting that miR-148a and miR-21-5p serve as contributing factors to bone fragility or as potential biomarkers of bone metabolic alterations in patients with type 1 DM [21]. However, only a few studies have shown direct roles for miRNAs in impaired fracture healing in patients with DM or in animal models of DM [22].…”
Section: Introductionmentioning
confidence: 99%